A Christian-Buddhist Dialogue on the Four Noble Truths - Munyua, Joseph Mwangi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2021)
For the first time, in the Vatican Council II (1962–65), the Catholic Church recognized non-Christian religions as entities that the Church should respect and with which Christians should enter into dialogue. Being on the same page, the World Council of Churches (WCC) affirms that from her initiation, the Church has been confessing that God is reconciling the world to Himself via His Son and has given us the ministry of reconciliation. Again, the WCC holds that, throughout history, the Church has been seeking to apply the basics of her faith to concrete situations in which she has been finding herself in her endless missiological journeys. Nowadays, the Church is called upon to empower her members to relate to people of other religions and to live as witnesses with others. These points justify the necessity of this article, which is entitled “A Christian-Buddhist Dialogue on the Four Noble Truths.” In the context of interreligious dialogue, this article seeks to explain the four Noble Truths of Buddhism in the light of Christian Soteriology. To that end, this article begins with a simplified explanation of the four Noble Truths of Buddhism after which it seeks to re-explain and re-express the same noble truths in the light of Christian Soteriology. Ultimately, this article reveals that Christians and Buddhists can borrow from each other towards enriching their respective soteriologies. Regarding its methodology, this article employs the review of the relevant literature, the principles of Nostra Eatate No. 2, the comparative method, and rational reflection.